The effects of smoking on the health and sleep of sportswomen. Issue 3 (September 1982) - Bale, P.; White, M.
Abstract : This survey studied the health and sleeping patterns of 92 physical education and sports science students highly involved in sport. A strong correlation was found between smoking and various complaints of ill health as well as between smoking and sleep duration and quality of sleep. The results suggest that there is a strong relationship between the constituents of tobacco smoke and poor sleeping habits.